2014
DOI: 10.2478/pjvs-2014-0109
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physiological and immunological parameters during the peripartum period in Zerasca sheep

Abstract: The aim of this study was to provide the picture of the dynamics of some blood parameters in the native Zerasca sheep breed during the peripartum period. Blood samples were collected from peripheral blood of 14 ewes at different times: from 21 d before lambing to 42 d after. Physiological and immunological parameters were evaluated: aspartate-aminotransferase, creatine kinase, lactate dehydrogenase, non-esterified fatty acids, total protein, total antioxidant capacity, free radicals, serum bactericidal activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Several studies have reported variable levels of oxidative stress during the transition period in dairy cows and have been recently reviewed [5]. Changes in redox status indicators were also found in a native sheep breed [6,7] and in a synthetic SCP (37.5% Polish sheep, 12.5% prolific breed, Romanowska or Finnsheep, 25% Suffolk, 25% Charollais) line [8] around lambing and during lactation. Studies in Red Syrian goats report a significant decrease in glutathione peroxidase (GPX) activity and albumin concentration during the peripartum, suggesting that animals experienced moderate oxidative stress during this period [9].…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have reported variable levels of oxidative stress during the transition period in dairy cows and have been recently reviewed [5]. Changes in redox status indicators were also found in a native sheep breed [6,7] and in a synthetic SCP (37.5% Polish sheep, 12.5% prolific breed, Romanowska or Finnsheep, 25% Suffolk, 25% Charollais) line [8] around lambing and during lactation. Studies in Red Syrian goats report a significant decrease in glutathione peroxidase (GPX) activity and albumin concentration during the peripartum, suggesting that animals experienced moderate oxidative stress during this period [9].…”
Section: Introductionmentioning
confidence: 97%
“…Cortisol increases estrogen concentration while decreasing progesterone concentration. It also increases oxytocin, which strengthens myometrial contractions (Nagel et al 2019, Akbulut andKal, 2022) and thus embryo implantation may be adversely affected. It has been reported that high cortisol levels cause failed embryo implantation in in-vitro fertilization (IVF) and embryo transfer (ET) in women (Magarelli et al 2009).…”
Section: Introductionmentioning
confidence: 99%